(untitled) (Journal of Parents and Teachers, 2026)
The importance of caring for families is a transformation that must begin at the personal and community levels, fostering a collective consciousness. It is necessary to balance work and family life, promote supportive laws, and create more humane work and social environments. Political and legal initiatives such as the Family Rights Act of 1991 are noteworthy.